1983
DOI: 10.1111/j.1476-5381.1983.tb10530.x
|View full text |Cite
|
Sign up to set email alerts
|

The source of thromboxane and prostaglandins in experimental inflammation

Abstract: 1Although cyclo-oxygenase products have been detected at inflammatory sites the tissue of origin remains uncertain. 2 Inflammatory exudates were collected from rats 4, 6, 8, 12 or 24 h after subcutaneous implantation of carrageenin-impregnated sponges.3 Concentrations of the cyclo-oxygenase products prostaglandin E2 (PGE2), 6-oxo-PGF,,, and thromboxane B2 (TXB2) in inflammatory exudates and serum (obtained from blood clotted at 370 C) were measured by specific radioimmunoassays. 4 TXB2 concentrations in exuda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 20 publications
2
49
0
1
Order By: Relevance
“…Importantly, we have shown that TXA 2 was produced significantly earlier than PGE 2 . This has been observed in fresh, nonadherent human monocytes (G.E.C., unpublished data); adherent human monocytes (24); and murine macrophages (25) as well as in animal models of inflammation (26). As was the case with exogenous AA, this finding also supports the proposal that TXA synthase, compared with PGE synthase, has a greater affinity for PGH 2 , whether the latter is synthesised from endogenous or exogenous AA.…”
Section: Discussionsupporting
confidence: 73%
“…Importantly, we have shown that TXA 2 was produced significantly earlier than PGE 2 . This has been observed in fresh, nonadherent human monocytes (G.E.C., unpublished data); adherent human monocytes (24); and murine macrophages (25) as well as in animal models of inflammation (26). As was the case with exogenous AA, this finding also supports the proposal that TXA synthase, compared with PGE synthase, has a greater affinity for PGH 2 , whether the latter is synthesised from endogenous or exogenous AA.…”
Section: Discussionsupporting
confidence: 73%
“…In the sponge model of inflammation, TXB2 is produced by migrating leukocytes and platelets do not contribute to TXB2 concentrations in the exudates (21). The similar potency of aspirin and salicylate in reducing TXB2 and PGE2 concentrations in inflammatory exudates suggests that the effects of both drugs are due to salicylate accumulating at the inflammatory site.…”
Section: Discussionmentioning
confidence: 82%
“…Serum TXB 2 is predominantly derived from platelets, with leukocytes being another source (Higgs et al 1983;Wallace and Ma 2001). In response to endogenous thrombin formation, i.e., clot formation, platelet COX-1 is maximally stimulated to produce TXA 2 , which is the major arachidonic acid metabolite produced by platelets, via COX-1, and one of the most potent platelet aggregating agent and vasoconstrictive substances known (Gilmer et al 2003;Kamath et al 2001;Smith 1989;Wallace and Ma 2001).…”
mentioning
confidence: 99%